A combined molecular docking and molecular dynamics simulation approach to probing the host–guest interactions of Ataluren with natural and modified cyclodextrins. Issue 2 (22nd January 2022) - Bayat, Farhad; Homami, Seyed Saied; Monzavi, Amirhossein; Talei Bavil Olyai, Mohamad Reza
ABSTRACT: The objective of this study was to apply molecular docking and molecular dynamics (MDs) simulation approaches to investigate the host–guest interactions between natural Cyclodextrins (CDs) (Alpha, Beta and Gamma Cyclodextrins) and some modified CDs (hydroxypropyl, sulfobutylether and randomly substituted methyl Beta Cyclodextrins) with Ataluren as a small molecule drug designed for diseases attributable to a nonsense mutation. Molecular docking results presented that randomly substituted methyl beta Cyclodextrin (RMBCD) has the highest binding affinity and Alpha Cyclodextrin (ACD) has the lowest binding affinity to Ataluren. According to the MDs simulation results, ACD and hydroxypropyl Cyclodextrin have not proper cavity for encapsulation of Ataluren. In contrast, Ataluren was totally included into the Beta Cyclodextrin (BCD), Gamma Cyclodextrin, sulfobutylether Beta Cyclodextrin (SBECD) and RMBCD due to appropriate interior capability. Moreover, MDs results showed that SBECD has the most conformational flexibility and BCD has the most conformational stability during simulation time. The results of this paper may open new paths to use this formulation for further researches in the delivery mechanism of hydrophobic pharmaceutical molecules.